Evolution of Eutrophication depending on Environmental Conditions: A Case Study in a Reservoir. - Álvarez, Xana; Valero, Enrique; Picos, Juan (European Journal of Sustainable Development, 2014)
In the last years, the phenomenon of eutrophication is affecting many river ecosystems. Besides being an environmental problem, it can also be a problem for human health. This study aims to explore how environmental parameters affect the concentration of green algae and cyanobacteria throughout the period from 2010 to 2013 in A Baxe reservoir (NW Spain). Factors such as temperature, rainfall and solar radiation influenced in the presence of the algae, as well as in its concentration. Being limiting factors in the cyanobacterial blooms. The highest value of chlorophyll occurs during the summer, with higher temperatures, coinciding with the dry season and with a light cycle of 15/9 light/dark cycle. We conclude that predictive models can be designed using the weather forecast that are currently available well in advance, with the result that water managers can know when it will be probable that a bloom take place as an early warning system, therefore they will have a protocol of action. Keywords: Freshwater ecosystems, cyanobacteria blooms, temperature, dry season.